2022
DOI: 10.1161/strokeaha.122.037448
|View full text |Cite
|
Sign up to set email alerts
|

Not Just Blood: Brain Fluid Systems and Their Relevance to Cerebrovascular Diseases

Abstract: troke research has largely focused on blood supply to the brain, particularly via large arteries leading from the heart, the muscular intracranial large arteries, large cerebral veins and venous sinuses, and more recently perforating arterioles, capillaries, and venules. However, these blood vessels only serve part of the brain's fluid management, nutrient delivery, and waste clearance system. The other, and until recently largely neglected, aspect of brain fluid and waste management is the system that flushes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We divided our regression models into potential (1) factors contributing to IFSHs and (2) outcomes associated with IFSHs. (1) In a first step, we performed univariate ordinal regression analyses with the total IFSH score (categories) as dependent variable and age, sex, years of education, and the dichotomous variables arterial hypertension, A+, T+, and AD pathology (A+ and T+ combined) as independent variables separately. Secondly, a multivariable ordinal regression analysis, which included all independent variables (except for AD pathology), was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We divided our regression models into potential (1) factors contributing to IFSHs and (2) outcomes associated with IFSHs. (1) In a first step, we performed univariate ordinal regression analyses with the total IFSH score (categories) as dependent variable and age, sex, years of education, and the dichotomous variables arterial hypertension, A+, T+, and AD pathology (A+ and T+ combined) as independent variables separately. Secondly, a multivariable ordinal regression analysis, which included all independent variables (except for AD pathology), was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebrospinal fluid (CSF) in the regions immediately superior to the cribriform plate, particularly those corresponding to the inferior frontal sulci, may display elevated signal intensities in T2-weighted fluid-attenuated inversion recovery (FLAIR) imaging [1]. The occurrence and extent of these hyperintensities, referred to as inferior frontal sulcal hyperintensities (IFSHs), have been proposed to be indicative of impaired CSF clearance and glymphatic dysfunction [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathology studies have also found more venous collagenosis associated with a higher WMH burden ( 7 ). More recently, a role for impaired glymphatic drainage has also been proposed for the pathogenesis of WMH lesions ( 37 ). Arteriolosclerosis is the most common pathologic correlate to WMH on imaging, ( 38 ) and arteriolar stiffening, or reduced compliance, impairs vasomotion and paravascular fluid clearance, thereby resulting in interstitial fluid accumulation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%